Optimal immunization strategies for Saanen goats against goatpox - Hossein Esmaeili; Seyed Mehdi Joghataei; Zeinab Hamidiya; Ehsan Baghal Arani; Amir pasha Shakeri; Zia Nosrat Rad; Mohammad Mahdi Safari (BMC Veterinary Research)
Abstract Background Goatpox is a highly contagious disease caused by the Capripoxvirus, primarily affecting sheep and goats. Breeds like the Saanen are particularly vulnerable, especially in enzootic areas, and face risks not only from the disease itself but also from adverse reactions to live attenuated vaccines. This study compares inactivated and attenuated vaccines to find the safest and most effective vaccination strategy for Saanen goats against the Goatpox Virus (GTPV). In this study, 375 pure-breed Saanen goats were strategically divided into four groups to explore the most effective vaccination protocols for combating combinations of vaccines. In contrast, one group remained unvaccinated as a control. After vaccination, the goats were challenged by exposure to naturally infected animals to assess the vaccines’ protective efficacy. PCR assays and the Virus Neutralization method were also conducted. Results Group G1 exhibited no adverse reactions following two inactivated vaccines, with only mild and brief signs observed in a small number of goats (2%) after the live attenuated vaccine. Group G2, which received an inactivated vaccine followed by a live attenuated vaccine, had mild lesions in 18.66% of the goats after vaccination. In contrast, Group G3, which only received the live attenuated vaccine, showed a high morbidity rate of 82% and a mortality rate of 22%, with severe clinical signs and Pox lesions. Following the challenge, no signs of GTPV infection were observed in Groups G1, G2, and G3, whereas the control group exhibited 100% morbidity and 72% mortality, confirming the vaccine’s protective efficacy. Conclusion This study found that a protocol using two inactivated vaccine doses at one-month intervals, followed by a live attenuated vaccine and annual boosters, effectively immunizes vulnerable breeds against GTPV without causing adverse reactions. This approach prevents complications and supports breeding in GTPV-enzootic regions.